Super-hydrophobic passivation liquid, super-hydrophobic passivation film on magnesium alloy surface and preparation method thereof
By developing a superhydrophobic passivation solution containing specific components, the problem of magnesium alloys being easily corroded in humid environments has been solved, simple and efficient surface treatment has been achieved, and the corrosion resistance and service life of magnesium alloys have been significantly improved.
Patent Information
- Application Number
- CN202411364271.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-29
AI Technical Summary
Magnesium alloys are prone to corrosion in humid environments, and existing surface treatment technologies have problems such as complexity, high cost and insufficient durability, making it difficult to meet the needs of industrial production.
A superhydrophobic passivation liquid was developed, containing aminopropyl heptaisobutyl cage polysilsesquioxane, methacryloyloxypropyl ladder polysilsesquioxane, manganese phosphate, cerium nitrate, and orthosilicon. Components such as ethyl acid ester and n-octadecyltrichlorosilane are sprayed or dip-coated to form a stable and dense superhydrophobic passivation film.
This method simplifies the surface treatment process of magnesium alloys, reduces costs, significantly improves the corrosion resistance and service life of magnesium alloys, and is suitable for industrial production.
Smart Images

Figure CN118880304B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal surface treatment, and in particular to a super-hydrophobic passivation liquid, a super-hydrophobic passivation film on the surface of a magnesium alloy and a preparation method thereof. Background Art
[0002] As a metal structural material, magnesium alloy has the characteristics of high specific modulus, high specific strength, high heat dissipation, excellent machinability, shock absorption, and castability. It is known as the "era metal" of the 21st century and is widely used in the fields of automobiles, aerospace, national defense, electronics, chemicals, and medical treatment. However, due to the active chemical properties of magnesium alloys, it is extremely susceptible to corrosion in humid, water and solution environments, and is easily adhered to by solid or liquid pollutants, which severely limits the scope of application of magnesium alloys. Considering that poor corrosion resistance is a major key issue restricting the development of magnesium alloys, and water is an indispensable participant in metal corrosion, magnesium alloys must be surface treated before they can be used in industry.
[0003] At present, the surface treatment technologies of magnesium alloys mainly include electroplating, electrophoresis, anodizing, chemical plating and organic coating. Although these methods can improve the corrosion resistance of magnesium alloys to a certain extent, there are still some problems in practical applications. For example, the electroplating and chemical plating processes are complicated and costly, the anodizing method has the problems of high processing temperature and high energy consumption, and the adhesion and durability of organic coatings are often insufficient. Therefore, it is particularly important to develop a simple, efficient, strong adhesion and excellent corrosion resistance magnesium alloy surface treatment method.
[0004] Superhydrophobic coatings have gradually attracted people's attention in recent years due to their excellent self-cleaning and anti-corrosion properties. Superhydrophobic materials have ultra-high contact angles (usually greater than 150°), which can effectively prevent water and other corrosive media from directly contacting the metal substrate, thereby greatly improving the corrosion resistance of the substrate. However, the preparation method of traditional superhydrophobic coatings usually requires multi-step processing or complex chemical reactions, which limits their large-scale application in industry.
[0005] CN112323116A discloses a preparation method of a magnesium alloy super-hydrophobic coating based on a zeolite imidazolate skeleton, proposes that micro-arc oxidation is used to treat a magnesium alloy to form a micro-nano rough structure, then a zeolite imidazolate skeleton structure is grown in situ on its surface, and finally a super-hydrophobic film is obtained after modification using n-octyltriethoxysilane. The invention has the advantage of utilizing the special structure of a zeolite imidazolate skeleton, so that the magnesium alloy super-hydrophobic coating based on a zeolite imidazolate skeleton is not restricted by the shape of the substrate, and has strong bonding strength. However, the invention has a problem of short service life and high cost.
[0006] CN114656864A discloses a super-hydrophobic magnesium alloy coating and a process thereof, and proposes a super-hydrophobic magnesium alloy coating composed of zinc oxide, multi-walled carbon nanotubes, and polycaprolactone. The advantage of the invention is that the use of multi-walled carbon nanotubes can effectively improve the surface quality and performance, improve the conductivity and heat dissipation functions. However, the invention usually has certain requirements for the preparation equipment and the operation is relatively complicated.
[0007] In summary, the prior art requires an efficient super-hydrophobic passivation treatment method for magnesium alloy surfaces, which simplifies the treatment process, reduces costs, and enhances the durability of the passivation film while providing excellent corrosion resistance to meet the needs of industrial production. To this end, the present invention provides a super-hydrophobic passivation solution, a super-hydrophobic passivation film on the surface of a magnesium alloy, and a preparation method thereof, which can form a stable and dense super-hydrophobic passivation film under simple processing conditions, and significantly improve the corrosion resistance of the magnesium alloy. Summary of the invention
[0008] In order to solve the problems of poor corrosion resistance of magnesium alloys in the prior art, difficulty in large-scale production of super-hydrophobic films on magnesium alloys and short lifespan, the present invention proposes a super-hydrophobic passivation liquid, a super-hydrophobic passivation film on the surface of a magnesium alloy and a preparation method thereof.
[0009] To achieve the above object, the present invention provides the following technical solutions:
[0010] A super-hydrophobic passivation liquid, which is composed of the following components by mass concentration: 2-5 g / L of aminopropyl heptaisobutyl cage-shaped polysilsesquioxane, 0.5-1 g / L of methacryloyloxypropyl trapezoidal polysilsesquioxane, 1-2 g / L of manganese phosphate, 1-2 g / L of cerium nitrate, 50-70 g / L of tetraethyl orthosilicate, 10-15 g / L of n-octadecyltrichlorosilane, 5-10 g / L of alcohol solvent, 0.5-1 g / L of acidic catalyst and deionized water;
[0011] Furthermore, the aminopropyl heptaisobutyl caged polysilsesquioxane is an organic and inorganic hybrid caged polysilsesquioxane with a molecular size of 1.5 nm and a structural formula of:
[0012] ;
[0013] Furthermore, the methacryloyloxypropyl trapezoidal polysilsesquioxane is an organic and inorganic hybrid trapezoidal material having both adhesiveness and structural stability, and its structural formula is:
[0014] ;
[0015] Furthermore, the alcohol solvent is one or more of ethanol, n-butanol, isobutanol or ethylene glycol;
[0016] Furthermore, the acidic catalyst is oxalic acid, nitric acid or phosphoric acid.
[0017] A method for preparing a super-hydrophobic passivation liquid comprises the following steps:
[0018] S1: aminopropyl heptaisobutyl cage-like polysilsesquioxane and methacryloxypropyl ladder-like polysilsesquioxane are sequentially added into deionized water and stirred to be fully mixed to form solution A;
[0019] S2: mixing solution A and ethanol, and sequentially adding ethyl orthosilicate and n-octadecyltrichlorosilane to the mixed solution and stirring to form solution B;
[0020] S3: adding manganese phosphate and cerium nitrate to solution B in sequence, stirring until completely dissolved, and adjusting the pH with an acidic catalyst, so that a transparent super-hydrophobic passivation liquid is prepared through a synergistic effect between manganese phosphate, cerium nitrate, ethyl orthosilicate, and n-octadecyltrichlorosilane;
[0021] Furthermore, the miscibility time in S1 is 20 to 30 minutes;
[0022] Further, the stirring time in S2 is 60 to 90 minutes;
[0023] Furthermore, the pH of the solution after adjustment with the acidic catalyst in S3 is 2.0-2.5;
[0024] Furthermore, the principle of the synergistic effect between manganese phosphate, cerium nitrate, ethyl orthosilicate and n-octadecyltrichlorosilane in S3 is as follows:
[0025] Furthermore, the hydrolysis of the tetraethyl orthosilicate in the system will generate SiO2 nanoparticles, which have a large specific surface area and activity; the n-octadecyltrichlorosilane is a low surface energy modifier, and the chlorine atoms in its molecules can undergo substitution reactions with the hydroxyl groups on the surface of the SiO2 nanoparticles, thereby achieving in-situ hydrophobic modification of the SiO2 nanoparticles. This modification process not only reduces the surface energy of the SiO2 nanoparticles, but also gives them hydrophobicity, so that the coating can form a more uniform and dense micro-nano structure after curing; the manganese phosphate is an inorganic salt that can form chemical bonds with the SiO2 nanoparticles to enhance the binding force between the particles, thereby improving the stability and durability of the coating. At the same time, manganese phosphate will have a regulatory effect on the micro-nano structure of the coating, further optimizing the hydrophobicity of the coating; the cerium nitrate promotes the uniform dispersion and interaction of the components in the coating through its unique chemical properties, thereby enhancing the overall performance of the coating;
[0026] In summary, the manganese phosphate, cerium nitrate, tetraethyl orthosilicate, and n-octadecyltrichlorosilane have the effects of synergistic coexistence and enhanced effects in the system, and jointly construct a stable coating system. The SiO2 nanoparticles generated by the hydrolysis of tetraethyl orthosilicate provide the basic skeleton for the coating; the hydrophobic modification of n-octadecyltrichlorosilane gives the coating hydrophobicity, which not only reduces the surface energy of the SiO2 nanoparticles, but also makes it easier for the coating to form the required micro-nano rough structure after curing; the addition of manganese phosphate and cerium nitrate further enhances the interaction and bonding force of the components in the coating, thereby enhancing the stability and durability of the coating, so that the coating can form a uniformly distributed, strong and dense micro-nanostructured super-hydrophobic passivation film after curing, thereby improving the overall performance and service life of the coating.
[0027] A method for preparing a super-hydrophobic passivation film on the surface of a magnesium alloy comprises the following steps: degreasing, wiping and drying the surface of the magnesium alloy, spraying, dipping, pouring or dipping the super-hydrophobic passivation liquid onto the surface of the magnesium alloy, and curing the super-hydrophobic passivation film;
[0028] Furthermore, the curing temperature is 100-120° C., and the curing time is 15-30 minutes.
[0029] Compared with the prior art, the present invention solves the problems of poor corrosion resistance of magnesium alloy, difficulty in large-scale production of magnesium alloy super-hydrophobic film and short life span, and the specific beneficial effects are:
[0030] (1) The raw material of the super-hydrophobic passivation liquid for the magnesium alloy surface provided by the present invention is green and environmentally friendly, is not limited by the size and shape of the magnesium alloy surface, has a long service life, and is simple to maintain and manage;
[0031] (2) The preparation process of the present invention is simple, does not require complicated production equipment, and is suitable for large-scale industrial production;
[0032] (3) The components in the super-hydrophobic passivation solution provided by the present invention jointly construct a stable coating system through synergistic coexistence and effect enhancement. The aminopropyl heptaisobutyl caged polysilsesquioxane combines the stability of the caged oligomeric silsesquioxane structure with the reactivity of the amino functional group, giving the coating thermal stability and hydrophobicity; the trapezoidal structure of the methacryloyloxypropyl trapezoidal polysilsesquioxane gives it excellent thermal decomposition temperature, tensile strength and wear resistance; the SiO2 nanoparticles generated by the hydrolysis of tetraethyl orthosilicate provide the basic skeleton for the coating; the hydrophobic modification of n-octadecyltrichlorosilane gives the coating hydrophobicity, which not only reduces the surface energy of the SiO2 nanoparticles, but also makes it easier for the coating to form the desired micro-nano rough structure after curing; manganese phosphate and cerium nitrate further enhance the interaction and bonding force of the components in the coating, thereby enhancing the stability and durability of the coating, so that the coating can form a uniformly distributed, strong and dense micro-nanostructured superhydrophobic passivation film after curing, thereby improving the overall performance and service life of the coating; the synergistic effect between the above components of the superhydrophobic passivation liquid improves the service life of the superhydrophobic passivation film and the corrosion resistance of the magnesium alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a diagram showing the super-hydrophobic performance of the super-hydrophobic passivation film to different types of water-based liquids;
[0034] Figure 2 The test results of wettability and durability of the composite coating prepared in Examples 1-4 are shown in FIG.
[0035] Figure 3 The graph is a test result of wettability and durability of the composite coating prepared in Comparative Examples 1-4. DETAILED DESCRIPTION
[0036] In order to make the technical solution of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the specification of the present invention. It should be noted that the following embodiments are only used to better understand the technical solution of the present invention and should not be understood as a limitation to the present invention.
[0037] Example 1.
[0038] Preparation of superhydrophobic passivation solution:
[0039] 3 g / L aminopropyl heptaisobutyl cage-like polysilsesquioxane and 0.6 g / L methacryloxypropyl trapezoidal polysilsesquioxane were added to deionized water in sequence and slowly stirred to fully mix for 25 minutes; then 56 g / L ethyl orthosilicate, 12 g / L n-octadecyltrichlorosilane, and 6 g / L ethanol were added in sequence and slowly stirred to react for 70 minutes; then 1.2 g / L manganese phosphate and 1.2 g / L cerium nitrate were added in sequence, slowly stirred until completely dissolved, and the pH value of the solution was adjusted to 2.4 with oxalic acid catalyst to obtain a transparent superhydrophobic passivation solution;
[0040] Preparation of super-hydrophobic passivation film on magnesium alloy surface:
[0041] The surface of the magnesium alloy was degreased, wiped clean and dried, and then the super-hydrophobic passivation liquid was dip-coated on the surface of the magnesium alloy. After curing at 110 ºC for 20 minutes, a super-hydrophobic passivation film was obtained.
[0042] 8 μL of water, coffee, Coca-Cola, milk, acid droplets (0.01 M) and alkali droplets (0.01 M) were respectively placed on the surface of the super-hydrophobic passivation film prepared in Example 1. The super-hydrophobic performance of the obtained super-hydrophobic passivation film to different types of water-based liquids is shown in FIG. Figure 1 , it can be seen that the contact angle of water-based liquid droplets on the surface of the passivation film is greater than 150º, which can effectively repel water-based liquids.
[0043] Example 2.
[0044] Preparation of superhydrophobic passivation solution:
[0045] 4 g / L aminopropyl heptaisobutyl cage-like polysilsesquioxane and 0.8 g / L methacryloxypropyl trapezoidal polysilsesquioxane were added to deionized water in sequence and slowly stirred to fully mix for 20 minutes; then 65 g / L ethyl orthosilicate, 14 g / L n-octadecyltrichlorosilane, and 7 g / L n-butanol were added in sequence and slowly stirred to react for 80 minutes; then 1.5 g / L manganese phosphate and 1.4 g / L cerium nitrate were added in sequence, slowly stirred until completely dissolved, and the pH value of the solution was adjusted to 2.4 with oxalic acid catalyst to obtain a transparent superhydrophobic passivation solution;
[0046] Preparation of super-hydrophobic passivation film on magnesium alloy surface:
[0047] The surface of the magnesium alloy was degreased, wiped clean and dried, and then the super-hydrophobic passivation liquid was sprayed onto the surface of the magnesium alloy. After curing at 120 ºC for 15 minutes, a super-hydrophobic passivation film was obtained.
[0048] Example 3.
[0049] Preparation of superhydrophobic passivation solution:
[0050] 4.5 g / L aminopropyl heptaisobutyl cage-like polysilsesquioxane and 0.9 g / L methacryloxypropyl trapezoidal polysilsesquioxane were added to deionized water in sequence and slowly stirred to fully mix for 25 minutes; then 65 g / L ethyl orthosilicate, 15 g / L n-octadecyltrichlorosilane, and 7 g / L ethanol were added in sequence and slowly stirred to react for 80 minutes; then 1.8 g / L manganese phosphate and 1.6 g / L cerium nitrate were added in sequence, slowly stirred until completely dissolved, and the pH value of the solution was adjusted to 2.4 with nitric acid catalyst to obtain a transparent superhydrophobic passivation solution;
[0051] Preparation of super-hydrophobic passivation film on magnesium alloy surface:
[0052] The surface of the magnesium alloy was degreased, wiped clean and dried, and then the super-hydrophobic passivation liquid was sprayed onto the surface of the magnesium alloy. After curing at 120 ºC for 20 minutes, a super-hydrophobic passivation film was obtained.
[0053] Example 4.
[0054] Preparation of superhydrophobic passivation solution:
[0055] 5 g / L aminopropyl heptaisobutyl cage-like polysilsesquioxane and 1.0 g / L methacryloxypropyl trapezoidal polysilsesquioxane were added to deionized water in sequence and slowly stirred to fully mix for 30 minutes; then 70 g / L tetraethyl orthosilicate, 15 g / L n-octadecyltrichlorosilane, and 8 g / L isobutyl alcohol were added in sequence and continued to be slowly stirred and reacted for 90 minutes; then 1.8 g / L manganese phosphate and 1.6 g / L cerium nitrate were added in sequence, slowly stirred until completely dissolved, and the pH value of the solution was adjusted to 2.4 with a phosphoric acid catalyst to obtain a transparent superhydrophobic passivation solution;
[0056] Preparation of super-hydrophobic passivation film on the surface of magnesium alloy: The surface of the magnesium alloy is degreased, wiped clean and dried, and then the super-hydrophobic passivation liquid is impregnated into the surface of the magnesium alloy. After curing at a temperature of 120 ºC for 20 minutes, a super-hydrophobic passivation film is obtained.
[0057] There is a synergistic effect between the raw materials used to prepare the super-hydrophobic passivation liquid and the super-hydrophobic passivation film. The super-hydrophobic performance is not only determined by a single raw material, but is the result of the synergistic effect of multiple raw materials. The wettability and durability test results of the composite coating prepared in the above embodiment are shown in FIG. Figure 2 shown.
[0058] Comparative Example 1.
[0059] The preparation method of this comparative example is the same as that of Example 1, except that the preparation step of the superhydrophobic passivation solution does not include aminopropyl heptaisobutyl caged polysilsesquioxane.
[0060] Comparative Example 2.
[0061] The preparation method of this comparative example is the same as that of Example 1, except that the preparation step of the superhydrophobic passivation liquid does not include methacryloxypropyl ladder polysilsesquioxane.
[0062] Comparative Example 3.
[0063] The preparation method of this comparative example is the same as that of Example 1, except that in the preparation step of the superhydrophobic passivation solution, 12 g / L of n-octadecyltrichlorosilane is replaced by 5 g / L of n-octadecyltrichlorosilane.
[0064] Comparative Example 4.
[0065] The preparation method of this comparative example is the same as that of Example 1, except that in the preparation step of the superhydrophobic passivation solution, 12 g / L of n-octadecyltrichlorosilane is replaced by 18 g / L of n-octadecyltrichlorosilane.
[0066] Comparison of the experimental results of Example 1 with those of Comparative Examples 1-4 shows that aminopropyl heptaisobutyl cage-like polysilsesquioxane, methacryloyloxypropyl trapezoidal polysilsesquioxane and n-octadecyltrichlorosilane are crucial to the durability of the super-hydrophobic passivation film on the surface of magnesium alloy. The synergistic effect between the raw materials for preparing the super-hydrophobic passivation film on the surface of magnesium alloy jointly determines the super-hydrophobic performance, wear resistance and water resistance of the coating, proving that the components in the coating complement each other, and the lack of a single component will significantly affect the durability of the super-hydrophobic coating. The wettability and durability test results of the composite coating prepared in the above comparative examples are shown in Figure 1. Figure 3 shown.
[0067] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A super hydrophobic passivation liquid, characterized in that, Measured by mass concentration, the composition is composed of the following components: 2-5 g / L aminopropyl heptaisobutyl cage polysilsesquioxane, 0.5-1 g / L methacryloyloxypropyl trapezoidal polysilsesquioxane, 1-2 g / L manganese phosphate, 1-2 g / L cerium nitrate, 50-70 g / L tetraethyl orthosilicate, 10-15 g / L n-octadecyltrichlorosilane, 5-10 g / L alcohol solvent, 0.5-1 g / L acidic catalyst and deionized water.
2. super hydrophobic passivating solution according to claim 1, is characterized in that, The alcohol solvent is one or more of ethanol, n-butanol, isobutanol or ethylene glycol.
3. super hydrophobic passivating solution according to claim 1, is characterized in that, The acid catalyst is oxalic acid, nitric acid or phosphoric acid.
4. A method for preparing a super-hydrophobic passivating solution as claimed in claim 1, characterized in that, The following steps are involved: S1: aminopropyl heptaisobutyl cage-like polysilsesquioxane and methacryloxypropyl ladder-like polysilsesquioxane are sequentially added into deionized water and stirred to be fully mixed to form solution A; S2: mixing solution A and ethanol, and sequentially adding ethyl orthosilicate and n-octadecyltrichlorosilane to the mixed solution and stirring to form solution B; S3: Manganese phosphate and cerium nitrate are added to solution B in sequence, stirred until completely dissolved, and the pH is adjusted with an acidic catalyst. A transparent super-hydrophobic passivation liquid is prepared through a synergistic effect between manganese phosphate, cerium nitrate, ethyl orthosilicate, and n-octadecyltrichlorosilane.
5. the preparation method of super-hydrophobic passivating solution according to claim 4, is characterized in that, The miscibility time described in S1 is 20 to 30 minutes.
6. the preparation method of super-hydrophobic passivating solution according to claim 4, is characterized in that, The stirring time described in S2 is 60 to 90 minutes.
7. The preparation method of super-hydrophobic passivating solution according to claim 4, wherein The pH of the solution after adjustment with the acidic catalyst in S3 is 2.0-2.
5.
8. A super hydrophobic passivation film on the surface of a magnesium alloy, characterized in that: The super-hydrophobic passivation liquid is solidified by using the super-hydrophobic passivation liquid as described in any one of claims 1 to 3 or the super-hydrophobic passivation liquid prepared by the preparation method as described in any one of claims 4 to 7.
9. A method for preparing a super-hydrophobic passivation film on a magnesium alloy surface as claimed in claim 8, characterized in that: The following steps are involved: The surface of the magnesium alloy is degreased, wiped clean and dried, and then the super-hydrophobic passivation liquid is sprayed, dipped, flow-coated or immersed on the surface of the magnesium alloy, and after curing, a super-hydrophobic passivation film is prepared.
10. The method for preparing a super-hydrophobic passivation film on a magnesium alloy surface according to claim 9, characterized in that: The curing temperature is 100-120°C; The curing time is 15 to 30 minutes.
Citation Information
Patent Citations
Preparation method of magnesium alloy super-hydrophobic coating based on zeolite imidazate framework
CN112323116A
Chitosan inorganic and organic composite passivation film good in film forming
CN106835106A
Surface conditioning composition and surface conditioning method
US20080041498A1